Math, asked by gautamgiri151, 8 months ago

(-8) -(+3)+(-1) - (-15)

Answers

Answered by viratkohli1805
4

Step-by-step explanation:

→ (-8) - (+3) + (-1) - (-15)

→ -8 -3 -1 + 15

→ 15 - 12

→ 3

Therefore, on solving (-8) - (+3) + (-1) - (-15), we will get 3 as our answer.

Please mark as “Brainliest Answer”.....

Answered by priyanshuShaurya
0

Answer:

Step-by-step explanation:

→ (-8) - (+3) + (-1) - (-15)

→ -8 -3 -1 + 15

→ 15 - 12

→ 3

Therefore, on solving (-8) - (+3) + (-1) - (-15), we will get 3 as our answer.

Please mark as “Brainliest Answer”.....

Similar questions